Finnish and Romanian students' understanding of Sustainable Development Goals in higher education (International Journal of Multidisciplinary Perspectives in Higher Education, 2025)
Educating students of all levels from kindergarten to higher education in Sustainable Development Goals (SDGs) is of high importance due to global goals for education as well as the life-long process of a single individual to become a better global citizen. Academic research and educational policies in recent years have focused a lot on pre-university levels and less emphasis was put onto higher education students’ perspective. Thus, the paper aims at analysing the students’ perceptions on what are the most important SDGs to learn about and describing students’ understanding of how much these SDGs are being integrated into their studies. Results coming from a quantitative survey for students will be presented. Context analyses in which certain SDGs were selected by students from Finland and Romania will be conducted and variables such as the socio-demographic profile of the respondents, degree-specific differences, along with the influence of other institutional actors (university strategy, educational policies, governmental policies, countries’ 2030 Agenda, etc.) were considered. Differences and communalities were presented.